Correlation Between Education and Age to the Perception of COVID-19 Vaccination - Lana Unwanah; Sitti Djannah; Dyah Suryani; Annisa Tristifanny; Andita Rahmanda; Hamza AbuHilail; Yanasta Yudo Pratama (Universitas Ahmad Dahlan, 2022)
Background: COVID-19, a pneumonia-like disease, started to spread at the end of 2019 and became a pandemic globally. Vaccination is one of the programs to reduce the severity of particular conditions, including COVID-19. However, in Indonesia, the response to COVID-19 vaccination remains low. This study aimed to assess the correlation between age and educational background to the perception of COVID-19 in Yogyakarta City, Indonesia. Method: This cross-sectional study was conducted from August to September 2021 at several vaccination centers in Yogyakarta City of Yogyakarta province. Total sampling was used to recruit participants during the mass vaccination period. Data were analyzed using univariate and bivariate analysis. Results: 1,068 participants joined this study, with an age average of 29.8. Most respondents graduated from senior high school 528 (49.4%). Bivariate analysis showed a significant correlation between education and knowledge about Adverse Events Following Immunization (p=0.01). Conclusion: Perception of the adverse event following immunization was significantly associated with education.